Problems of law enforcement in Vietnam : - Nguyen, Thi Phuong Loan (Unversity of Bonn, 2010)
this book provives the result of the research that analyzes contradictions and conflicts between the national and local regulations, specifically in the field of wastewater management. It will be discussed how the provincial government of Can Tho City enforces the national law on water resource management and how national regulations are interpreted and newly defined in the context of local governance. Furthermore, the study aims at contributing to the debate on how to create a comprehensive and coherent legal framework of the water sector at both national and local scale of government